2010
DOI: 10.1080/10410236.2010.521904
|View full text |Cite
|
Sign up to set email alerts
|

A Content Analysis of News Coverage of Skin Cancer in China Newspapers

Abstract: China has the largest population in the world today. Recent epidemiology investigation showed a significant increase in the incidence of skin cancer in China. However, little is known about the content of skin cancer articles in Chinese newspaper coverage. To analyze the skin cancer issues in the newspaper media over an eight-year period from 2000 through 2007 in China, we performed a preliminary search of articles titled by "skin cancer" in Chinese important newspapers database. There were 134 articles about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Skin cancer, the most prevalent cancer worldwide, can be broadly divided into melanoma and nonmelanoma skin cancer (which includes basal and squamous cell carcinoma), depending on the cell type. Epidemiological studies show that the incidence of skin cancer has increased at an alarming rate in previous decades not only in Western countries but also in Asia 1–3 . The World Health Organization claims that one in three cancer cases are skin related, which stresses the global importance of skin cancer prevention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin cancer, the most prevalent cancer worldwide, can be broadly divided into melanoma and nonmelanoma skin cancer (which includes basal and squamous cell carcinoma), depending on the cell type. Epidemiological studies show that the incidence of skin cancer has increased at an alarming rate in previous decades not only in Western countries but also in Asia 1–3 . The World Health Organization claims that one in three cancer cases are skin related, which stresses the global importance of skin cancer prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies show that the incidence of skin cancer has increased at an alarming rate in previous decades not only in Western countries but also in Asia. [1][2][3] The World Health Organization claims that one in three cancer cases are skin related, which stresses the global importance of skin cancer prevention. Basal cell carcinoma (BCC) is the most common type of keratinocyte tumor, exhibiting slow growth rate and spreading rarely.…”
Section: Introductionmentioning
confidence: 99%
“…Six keywords, including skin cancer, melanoma, basal cell cancer, squamous cell cancer, sun protection and sun safety, were searched in the 72 issues (12 issues per magazine) through online archival databases of the six magazines. The keywords were adopted from the study on news coverage of skin cancer by Liu et al 61 The search of the keywords within the timeframe initially yielded 28 articles. As the study aims to explore the portrayals of skin cancer, articles which discussed the health issue in a marginal manner or merely mentioned the keywords were excluded for analysis.…”
Section: Methods Data Collectionmentioning
confidence: 99%
“…Of those studies examining the amount and/or type of news coverage, a key focus was on news coverage over time (n=71), particularly in terms of changes in the amount of coverage received and key themes within the coverage (e.g. [26,28,29,32,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]). For example, studies have found that the amount of news coverage of obesity [28,29], cancer [58,59], and smoking-related harms [32,60] have increased over time.…”
Section: Content Of News Mediamentioning
confidence: 99%